New species and records of Caenidae Newman, 1853 (Insecta: Ephemeroptera) from Rondônia State, Northern Brazil - Nascimento, Stênio R.s.; Cruz, Paulo V.; Lima, Lucas R.c.; Lima, Cláudia R.t.; Hamada, Neusa; Ale-Rocha, Rosaly (Zootaxa, 2023)
Caenidae is a globally widespread family, inhabiting a variety of aquatic habitats. In South America, only 35 species are recognized, maybe as a consequence of the few studies until the first decade of the 21st century. Despite recent advances, large portions of Brazil, such as Rondônia State, are still characterized by Linnean and Wallacean shortfalls. Rondônia is an area predicted to have high mayfly richness, but with no record of Caenidae. From this perspective, the objective of this study is to provide the first access to primary biodiversity data of Caenidae (Ephemeroptera) from Rondônia. As result, we report five species (Brasilocaenis elidioi, Brasilocaenis irmleri, Caenis chamie, Caenis fittkaui, Latineosus sigillatus) and describe a new species based on all life stages (Caenis urupa sp. nov.).